Meningkatkan Kemampuan Pemecahan Masalah Matematika Menggunakan Model Kooperatif Tipe Jigsaw Pada Materi Perbandingan - Nurkamiden, Fikran; Pomalato, Sarson W. Dj.; Zakiyah, Siti (Scimadly Publishing, 2025)
The purpose of this study was to improve students' mathematical problem-solving abilities through the Jigsaw Cooperative Type model in the comparison material. This research is a type of classroom action research. This research consists of two cycles. The research subjects were students in class VII–5 for the academic year 2022–2023, with a total of 28 students, consisting of 17 male students and 11 female students. The techniques used in data collection were teacher observation sheets, student observation sheets, and tests of students' mathematical problem-solving abilities. This research consists of two cycles. The results showed that the test results for students' problem-solving abilities in cycle I, namely 46.43%, had a good minimum criterion, and in cycle II, the minimum criteria increased to 85.71. From observations of teacher activities managing learning, there was an increase in cycle I, namely 50%, where the minimum criteria were good, and in cycle II, namely 87.5%. The results of observations of student activities experienced an increase from cycle I, namely 50%, where the minimum criteria were good, to cycle II, namely 87.50%. This means that learning using a jigsaw cooperative model in comparative material can improve students' mathematical problem-solving abilities.